Gendered Morality: Classical Islamic Ethics of the Self, Family, and Society by Zahra Ayubi (American Journal of Islam and Society, 2020)
Since the 1990s, the field of Islamic studies has seen a veritable flood of scholarship addressing issues of gender in the pre-colonial Islamic past. Some of these contributions, like the works of Amira Sonbol and Judith Tucker, contributed to the reconstruction of the history of women and the family in Muslim-majority societies (a trend that has been continued by work such as that of Yossef Rapaport). More recently, scholars such as Kecia Ali, Mohammad Fadel, Hina Azam, and Behnam Sadeghi have offered deep and ambitious analyses of the gendered logic of legal argumentation in works of fiqh.To read the full book review, download the PDF file on the right.